Targeting and Efficacy of Novel mAb806-Antibody-Drug Conjugates in Malignant Mesothelioma - Puey-Ling Chia; Sagun Parakh; Ming-Sound Tsao; Nhu-An Pham; Hui K. Gan; Diana Cao; Ingrid J. G. Burvenich; Angela Rigopoulos; Edward B. Reilly; Thomas John; Andrew M. Scott (MDPI AG, 2020)
Epidermal growth factor receptor (EGFR) is highly overexpressed in malignant mesothelioma (MM). MAb806 is a novel anti-EGFR antibody that selectively targets a tumor-selective epitope. MAb806-derived antibody drug conjugates (ADCs), ABT-414, ABBV-221 and ABBV-322, may represent a novel therapeutic strategy in MM. EGFR and mAb806 epitope expressions in mesothelioma cell lines were evaluated using an array of binding assays, and the in vitro cell effects of ABT-414 and ABBV-322 were determined. In vivo therapy studies were conducted in mesothelioma xenograft and patient-derived xenograft (PDX) tumor models. We also performed biodistribution and imaging studies to allow the quantitative targeting of MM by mAb806 using a 89Zr-labeled immunoconjugate-ch806. A high EGFR expression was present in all mesothelioma cell lines evaluated and mAb806 binding present in all cell lines, except NCIH-2452. ABT-414 and ABBV-322 resulted in significant tumor growth inhibition in MM models with high EGFR and mAb806 epitope expressions. In contrast, in an EGFR-expressing PDX model that was negative for the mAb806 epitope, no growth inhibition was observed. We demonstrated the specific targeting of the mAb806 epitope expressing MM tumors using 89Zr-based PET imaging. Our data suggest that targeting EGFR in MM using specific ADCs is a valid therapeutic strategy and supports further investigation of the mAb806 epitope expression as a predictive biomarker.